2021
DOI: 10.46827/ejpe.v6i10.3571
|View full text |Cite
|
Sign up to set email alerts
|

Potential Factors in Engaging Physical Activity Beyond Physical Education Class

Abstract: The study determined the potential factors in the engagement of students’ physical activity beyond regular physical education class. Participants were 476 secondary students aged between 16 and 22 from randomly selected public and private schools of Metro Cebu, Philippines. Cross-sectional survey design was used to examine the potential factors of students in engaging physical activity such as autonomy support, behavioural regulations, and intentions outside school. The study highlighted on the presence of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It was found out that interventions targeting internal motivation, such as goal setting and self-monitoring, were more effective in promoting physical activity engagement than interventions targeting external motivation, such as rewards or punishments (Ng et al,2012). Furthermore, creating supportive environments that promote internal motivation, such as providing opportunities for social support and autonomy, can promote movement capability and improve overall health outcomes (Garcia, Bojos & Sy, (2021). All the informants were happy to engage in physical activity.…”
Section: Internal Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found out that interventions targeting internal motivation, such as goal setting and self-monitoring, were more effective in promoting physical activity engagement than interventions targeting external motivation, such as rewards or punishments (Ng et al,2012). Furthermore, creating supportive environments that promote internal motivation, such as providing opportunities for social support and autonomy, can promote movement capability and improve overall health outcomes (Garcia, Bojos & Sy, (2021). All the informants were happy to engage in physical activity.…”
Section: Internal Motivationmentioning
confidence: 99%
“…Recently, there are studies that shown possible relationship between movement capability and physical activity. It is believed that individuals with higher motivation and support from the school and parents are more likely to engage in regular physical activity (Garcia, Bojos, & Sy, 2021), blood types (Garcia & Canillas, 2023), and biological factor and psychological factor (Garcia,2022). Thus, improving movement capability may effectively increase physical activity levels and promote overall health (Warburton, Nicol, & Bredin, 2006).…”
Section:  Introductionmentioning
confidence: 99%
“…Even before pandemic, there are several studies already proved that physical fitness of an individual can be augmented if certain interventions will be provided and/or facilitated. It has showed that students' participation in physical activity increases its fundamental movement skills [7] and when there are physical resources provided, internal regulation is clear, students' intentions is strong and when they feel supported and motivated [8].…”
mentioning
confidence: 99%